Kondisi Permukaan Air Tanah dengan dan tanpa peresapan buatan di daerah Bandung: Hasil Simulasi Numerik - Hutasoit, Lambok M. (Indonesian Journal on Geoscience, 2009)
http://dx.doi.org/10.17014/ijog.vol4no3.20093Significant groundwater level drawdown caused by groundwater abstractions has been reported to occur in Bandung and its surrounding area. One potential method to recover the groundwater condi- tion is artifical recharge, considering high quantity of rainfall in this area. In this research, numerical simulation has been performed in order to predict groundwater condition in the next five years, if: 1) no recovery action is taken (do-nothing) (Scenario 1), and 2) artificial recharge is performed (Scenario 2). Hydrogeological condition reconstruction  required for physical model development  reveals that the main aquifer in the researched area is Cibeureum Formation, which comprises volcanic fans; the main aquitard is Kosambi  Formation, crasisting of lake deposit, whilst the hydrogeologic basement in the research area is the Cikapundung Formation, other Quaternary volcanic rocks, except the Cibeureum Formation, and Tertiary rock units. The recharge area is the areas where the Cibeureum Formation crops out. The result of numerical simulation of Scenario 1 shows that if there is no recovery action taken on the groundwater condition, then in year 2013 the Critical Zone will increase about 116 % and the Damage Zone will increase about 570 %. The result of this scenario also shows that there will be groundwater mining in several areas in the Damage Zone with the total area of 244 km2 or 41 % of the total  confined aquifer area. Result of the numerical simulation of Scenario 2 shows that  the artificial recharge in the above Critical and Damage Zones will effectively recover groundwater condition in year 2013 which means is, the whole area becomes Safe Zone. The amount of the artificial recharge is about 164 million m3/year and it started from year 2009. The artificial recharge means recharge well, surface reservoir, or recharge ditch where the Cibeureum Formation crops out, or injection well where this formation does not crop out.